Možnosti reklamy firmy na veletrzích - Budínská, Lucie (Vysoké učení technické v Brně. Fakulta podnikatelská, 2010)
Tato bakalářská práce je zaměřena na propagaci firmy EXCON, a.s. na veletrzích. Obsahuje informace o analyzované firmě, o všeobecné reklamě a reklamách na veletrzích. Způsoby a ukázky propagace na veletrhu, možnosti jak expozici připravit a realizovat, aby splnila všechny požadované cíle. Především jde o navržení optimální skladby reklamy na veletrzích.

The bachelor's thesis is focused on promotion EXCON copmany, Ins. at the trade fairs. It contains information about the company being analyzed, the general advertising and advertising at trade fairs. Methods and examples of promotion at the trade fair, ways to prepare and implement the exhibition to meet all the required targets. Above all this bachelor's thesis is focused on proposition of the optimal structure of advent at the trade fairs.
Possibilities of Companies Advertisement of Fairs
Keywords: podpora prodeje; reklama; prezentace; dobré jméno; marketing; stánek; zákazníci; výstavy; veletrhy; propagace; příprava; konkurence; expozice; přípravy; firma; sales promotion; advertisement; presentation; goodwill; marketing; stand; costumers; exhibitions; advertising; preparation; competition; exposure; training; company